THE ART OF PUBLIC SPEAKING: AN ACCOUNT OF THREE SELECTED NAMIBIAN PUBLIC SPEAKERS, PEYA MUSHELENGA, SAM SHIVUTE AND NDANGI IILEKA (Journal for Studies in Humanities and Social Sciences, 2022)
A good speech is given when a speaker knows and understands the needs of his/her audience.  When a speaker fails to have effective oral communication with an audience, they are unlikely  to achieve their communicative purposes. Literature shows that successful public speakers use  rhetoric to persuasively convey their messages to their audiences. In this study, persuasive  strategies in public speaking are investigated through rhetorical analysis by interviewing orally  these three participants: Peya Mushelenga, Sam Shivute and Ndangi Iileka. The study used Burke’s (1969) theory of identification by outlining the possible occurrences of identification. This theory claims that whenever a speaker tries to persuade, identification takes place. The  study’s findings, through the different experiences and narratives of these three participants, revealed that listeners are persuaded when speakers use literary devices based on the  communicative purposes of their speeches. The main purposes of these participants’ speeches are often to inform, motivate and to entertain, respectively. The conclusions drawn from this  study points to the relevance of Burke’s theory of identification regarding the addressees and  audiences which young, rising public speakers should bear in mind.
Keywords: public speaking; persuasion; Burke’s identification theory; public speakers; Namibia